Residual effects of composted sewage sludge on nitrogen cycling and plant metabolism in a no-till common bean-palisade grass-soybean rotation - Silva, Mariana Bocchi da; Camargos, Liliane Santos de; Teixeira Filho, Marcelo Carvalho Minhoto; Souza, Lucas Anjos; Coscione, Aline Renée; Lavres, José; Abreu-Junior, Cassio Hamilton; He, Zhenli; Zhao, Fengliang; Jani, Arun Dilipkumar; Capra, Gian Franco; Nogueira, Thiago Assis Rodrigues (Frontiers in Plant Science, 2023)
Introduction and aims In the context of increasing population and decreasing soil fertility, food security is one of humanity’s greatest challenges. Large amounts of waste, such as sewage sludge, are produced annually, with their final disposal causing environmental pollution and hazards to human health. Sludge has high amounts of nitrogen (N), and, when safely recycled by applying it into the soil as composted sewage sludge (CSS), its residual effect may provide gradual N release to crops. A field study was conducted in the Brazilian Cerrado. The aims were to investigate the residual effect of successive applications of CSS as a source of N in the common bean (Phaseolus vulgaris L. cv. BRS Estilo)-palisade grass (Urochloa brizantha (A.Rich.) R.D. Webster)-soybean (Glycine max L.) rotation under no-tillage. Additionally, N cycling was monitored through changes in N metabolism; the efficiency of biological N2 fixation (BNF) and its implications for plant nutrition, development, and productivity, was also assessed. Methods The experiment consisted of a randomized complete block design comparing four CSS rates (10, 15, 20, and 25 Mg ha-1, wet basis) to a control treatment (without adding mineral or organic fertilizer) over two crop years. Multiple plant and soil analyses (plant development and crop yield, Falker chlorophyll index (FCI), enzymatic, biochemical, 15N natural abundance, was evaluated, root and shoot N accumulation, etc.) were evaluated. Results and discussion Results showed that CSS: i) maintained adequate N levels for all crops, increasing their productivity; ii) promoted efficient BNF, due to the stability of ureide metabolism in plants and increased protein content; iii) increased the nitrate content and the nitrate reductase activity in soybean; iv) affected urease activity and ammonium content due to changes in the plant’s urea metabolism; v) increased N accumulation in the aerial part of palisade grass. Composted sewage sludge can be used as an alternative source to meet crops’ N requirements, promoting productivity gains and N cycling through forage and improving N metabolism.